Students Learning About Science by Investigating an Unfolding Pandemic - Camillia Matuk; Rebecca Martin; Veena Vasudevan; Kim Burgas; Kim Chaloner; Ido Davidesco; Sushmita Sadhukha; Yury Shevchenko; Engin Bumbacher; Suzanne Dikker (SAGE Publishing, 2021)
We explored the COVID-19 pandemic as a context for learning about the role of science in a global health crisis. In spring 2020, at the beginning of the first pandemic-related lockdown, we worked with a high school teacher to design and implement a unit on human brain and behavior science. The unit guided her 17 students in creating studies that explored personally relevant questions about the pandemic to contribute to a citizen science platform. Pre-/postsurveys, student artifacts, and student and teacher interviews showed increases in students' fascination with science-a driver of engagement and career preference-and sense of agency as citizen scientists. Students approached science as a tool for addressing their pandemic-related concerns but were hampered by the challenges of remote schooling. These findings highlight both the opportunities of learning from a global crisis, and the need to consider how that crisis is still affecting learners.